NF-κB-mediated transcriptional upregulation of TNFAIP2 by the Epstein–Barr virus oncoprotein, LMP1, promotes cell motility in nasopharyngeal carcinoma - Chen, C-C; Liu, H-P; Chao, M; Liang, Y; Tsang, N-M; Huang, H-Y; Wu, C-C; Chang, Y-S (Oncogene, 2014)
Nasopharyngeal carcinoma (NPC), which is closely associated with Epstein–Barr virus (EBV), is a metastasis-prone epithelial cancer. We previously showed that tumor necrosis factor α-induced protein 2 (TNFAIP2) is highly expressed in NPC tumor tissues and is correlated with metastasis and poor survival in NPC patients. However, the underlying mechanism remains unclear. In this study, we demonstrate that the EBV oncoprotein, latent membrane protein 1 (LMP1), can transcriptionally induce TNFAIP2 expression via NF-κB. Quantitative RT–PCR and western blotting revealed that LMP1 induces TNFAIP2 expression through its C-terminal-activating region (CTAR2) domain, which is required for transduction of NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) signaling. Inhibition of NF-κB activation or depletion of p65 (a component of NF-κB) by RNA interference abolished the LMP1-induced expression of TNFAIP2, whereas ectopic expression of p65 was sufficient to induce TNFAIP2 expression. Luciferase reporter assays showed that LMP1 transcriptionally induces TNFAIP2 expression through a newly identified NF-κB-binding site within the TNFAIP2 promoter (−3 869 to −3 860 bp). Immunohistochemical analysis of NPC biopsy specimens further revealed a significant correlation between the protein levels of TNFAIP2 and activated p65 ( R =0.689, P <0.001), indicating that our findings are clinically relevant. Immunofluorescence microscopy and co-immunoprecipitation assays showed that TNFAIP2 associates with actin and is involved in the formation of actin-based membrane protrusions. Furthermore, transwell migration assays demonstrated that TNFAIP2 contributes to LMP1-induced cell motility. Collectively, these findings provide novel insights into the regulation of TNFAIP2 and its role in promoting NPC tumor progression.